Minor and Major Sentence Structure in Kaili Language Rai Dialect - Rifdah Nur Zahiidah; Felicia Elsadora Moran; Amelia Zahra; Annisa Miftahul Rezkya (Global Education Journal, 2026)
Language is an arbitrary, productive, dynamic, diverse, and used sound symbol system by humans as a means of communication. This study aims to describe the structure of minor and major sentences in the Kaili language Rai dialect. This research uses a descriptive qualitative method. Data were collected using the observation method and the conversational method with involvement observation, recording techniques, face-to-face conversation, and note-taking techniques. Data analysis was conducted using the identity method with translational technique. The results show that minor sentences in the Kaili language Rai dialect are divided into two types: minor sentences in the form of words (5 data) which include exclamations, commands, and questions, as well as minor sentences in the form of phrases (5 data) which include greeting phrases, prohibitions, commands, hopes, and warnings. Meanwhile, major sentences are divided into three types: simple major sentences with S-P-Adv pattern (5 data), compound major sentences with Independent Clause 1 + Conjunction 'ante' + Independent Clause 2 pattern (5 data), and complex major sentences with independent clause + subordinating conjunction ('waktu' meaning 'when') + adverbial clause pattern (5 data).